Developing Professional Teachers in the Digital Age Through ICT Learning in the Cijeungjing Regional Office - Nasrulloh, Iman; Solihati, Essy; Nugraha, Wildan (Fakultas Kewirausahaan Universitas Garut, 2024)
This Community Service (PkM) activity was carried out to enhance teachers' professionalism in the digitalization era through the utilization of Information and Communication Technology (ICT)-based learning. This program was motivated by the lack of ICT skills among teachers, which hinders the optimal integration of technology into the teaching process. The implementation method included socialization on the importance of digitalization, training on ICT application in teaching, and practical mentoring to ensure teachers could apply the acquired skills. The results revealed a significant improvement in teachers’ understanding and skills in utilizing ICT, which positively impacted the quality of lesson planning and instructional delivery. Therefore, this training contributes to strengthening teachers' competencies in facing the challenges of 21st-century education.